Barriers of persistent long-lasting insecticidal nets utilization in villages around Lake Tana, Northwest Ethiopia: a qualitative study - Asmamaw Malede; Mulugeta Aemero; Sirak Robele Gari; Helmut Kloos; Kassahun Alemu (BMC, 2019)
Abstract Background Malaria remains a major public health problem in Ethiopia. The use of LLINs is an effective approach to reducing transmission. Persistent use of LLINs is determined by numerous factors. Quantitative studies have assessed LLIN ownership and utilization, but the behavioral, socio-cultural, socioeconomic and net distribution contexts that impact their use have not been examined in depth. This study aimed to explore barriers of persistent LLIN use among communities around Lake Tana. Methods Twenty-three community residents who owned LLINs (15) or not (8) during the study period and 38 key informants were interviewed from April to June 2017. Phenomenological study was employed to explore the local contexts and factors that influence persistent use of LLINs. Individuals were purposefully selected to capture different views. Community residents were selected based on their permanent residence and LLIN use experience. Key informants were health extension workers, local leaders, students, and health professionals. The data were managed using QSR International NVivo Version 10 software and coded, and themes were identified. Results Killing ability of nets against arthropods other than mosquitoes reportedly made use of LLINs a favored malaria prevention method despite their ineffectiveness after 3 months. Conical nets were preferred due to their compatibility with varied sleeping structures. Numerous factors influenced persistent use, notably erroneous perceptions about LLINs, malaria and mosquitoes; bedbug infestation; inconvenience; unintended uses; distribution problem of nets; and socio-cultural and economic factors. Unintended uses were often associated with local needs and seldom linked with social issues and deficiencies in information about malaria and LLINs. Collateral benefits were considered important, principally in terms of disinfestation of bedbugs. Conclusions Non-persistent LLIN use was associated with inconvenient bed net design and early damage; non-potency of the insecticide against other arthropods; facilitation of bedbug infestation; unintended uses; wrong perceptions about malaria, mosquitoes, and LLINs; and inadequate follow-up regarding LLINs utilization. Distribution of conical nets and provision of adequate information on LLINs and malaria may promote persistent use. Using an insecticide that also kills arthropods other than mosquitoes may reduce unintended uses and increase persistent use.